2019
DOI: 10.1039/c9sc02773d
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the rearrangement of atomic configurations during the conversion of FAU zeolite to CHA zeolite

Abstract: Interzeolite conversion from FAU to CHA results in massive atomic rearrangements in their common structural motif to form a stable atomic configuration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 54 publications
3
60
0
Order By: Relevance
“…CHA 18 ) indicate the conservation of short-range Al distributions, as seen throughout FAU-to-CHA transformation. 40 A similar conclusion was drawn by our group for a high Si FAUto-CHA IZC system (Devos et al), 24 where we demonstrated that the very fast (<3h) procedure runs via an intermediate Al-rich phase prior to nucleation, as seen in a temporal analysis of liquid and solid fractions. The resulting crystalline Si-rich CHA (Si/Al up to 35) shows a remarkably high content of acid site (Al) proximity as deduced from cobalt (divalent cation) titration.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…CHA 18 ) indicate the conservation of short-range Al distributions, as seen throughout FAU-to-CHA transformation. 40 A similar conclusion was drawn by our group for a high Si FAUto-CHA IZC system (Devos et al), 24 where we demonstrated that the very fast (<3h) procedure runs via an intermediate Al-rich phase prior to nucleation, as seen in a temporal analysis of liquid and solid fractions. The resulting crystalline Si-rich CHA (Si/Al up to 35) shows a remarkably high content of acid site (Al) proximity as deduced from cobalt (divalent cation) titration.…”
Section: Introductionsupporting
confidence: 89%
“…12,24 Therefore, a second influence on Al (acid site) distribution was proposed, based on fast growth kinetics: the role of nucleation and assembly pathways (II), as suggested from the earlier work of our group on FAU-to-CHA ([TMAda] IZC ). 24 From the generic model proposed for IZC evolution (section 4.2, Scheme 1), and literature, it can be suggested that specific Al dense regions may persist throughout the evolution 40 and rationalized that fast crystallization kinetics (e.g. Al-'loving' IZC systems, 4.1.)…”
Section: Understanding Genesis and Evolution Of Acid Site Arrangements During Synthesismentioning
confidence: 99%
“…In fact, the assumptions about their existence have been derived from indirect indicators, based on the correlation between the properties of the starting and resulting zeolites. For instance, in a study of the FAU-to-CHA transformation mechanisms, the 29 Si MAS NMR spectra of the starting and resulting structures were recorded [65]. Because all zeolite lattice atoms are PETROLEUM CHEMISTRY Vol.…”
Section: Investigation Of Intermediate Structures Formed During Interzeolite Transformationmentioning
confidence: 99%
“…Muraoka et al combined solid-state 29 Si NMR analysis with high-throughput computational modeling to track the local coordination environments of aluminum atoms in the interzeolite conversion from FAU to CHA. 33 Mlekodaj et al carried out experimental investigations into interzeolite conversions from FAU, LTA and MFI to CHA, and their results indicated that the starting zeolites, regardless of the degree of structural similarity with the final one, should be disintegrated into linear or branched aluminosilicate oligomers during the interzeolite conversion. 34 These works demonstrated that the common structural motif between the starting and the end zeolites no longer remains intact, but a specific rearrangement of silicate and aluminate species takes place.…”
Section: Introductionmentioning
confidence: 99%